Effect of torrefaction pretreatment on combustion behaviour of different agricultural wastes - Duranay, Neslihan; Yilgin, Melek; Aydoğmuş, Ercan (Yildiz Technical University, 2023)
In this study, which was carried out to investigate the effect of the torrefaction process on the combustion behaviour of agricultural wastes, almond hulls and shells, olive seeds and corn stalks were used. The samples, dried in a laboratory atmosphere, were torrified at 300±5 ºC for 41 minutes. The change in fuel properties was determined by making proximate analyses of the solid product obtained after the process and compared with the raw sample. The effects of the torrefaction process on the combustion behaviour of agricultural wastes of different structures were investigated by burning the 1±0.15 g weighted raw and torrefied samples at 700 ºC furnace initial temperature in a fixed bed system. Biochars containing higher fixed carbon were obtained with the torrefaction process applied to agricultural waste, and it was determined that this caused biochars to burn more efficiently and for a longer time than raw biomass. As a result, it was determined that biochar with better properties was produced by the torrefaction process applied to agricultural wastes and it was suitable for burning in solid fuel combustion systems. Thus, biochar obtained will both contribute to the country's economy and add value to agricultural wastes that cause problems during storage, transportation, loading into the burning system, and combustion. © 2024 Royal Institution of Naval Architects. All rights reserved.
Keywords: Agricultural waste; Combustion; Energy recovery; Torrefaction